Dentin Thickness at Danger Zone and Canal Morphology of Maxillary Molars - Deniz Yanik; Ahmet Mert Nalbantoğlu (University of Zagreb. School of Dental Medicine, 2022)
Objectives: Dentin thickness in concave areas of the root creates risk for complications such as strip perforation during endodontic treatment. The study aims to examine dentin thickness of the danger (DZ) and safety zone (SZ), canal configuration, and the presence of isthmus in the mesiobuccal root of maxillary molars. Material and methods: Conebeam Computed Tomography (CBCT) images of 1251 teeth belonging to 642 patients were retrospectively reviewed. The dentin thicknesses at DZ and SZ in maxillary molars with one (MB) or two mesiobuccal canals (MB1, MB2) were measured at the 3 mm apical to the furcation level. Vertucci's canal configurations and the isthmus rate were recorded. The Chi-square test and The Student's t-test were performed. Results: MB2 rate was higher in maxillary first molars (61.68%) than second molars (39.36%). Isthmus rates were 27.3% and 44.11% in first and second molars. DZ thickness was thinner than the dentin thickness in the SZ in both first and second molars with one or two mesial canals (p< 0.05). In teeth with single canal, the mean DZ thickness was 0.88mm. In teeth with two canals, the mean DZ thicknesses were 0.83mm and 0.80mm for MB1 and MB2 canals, respectively.Conclusion: MB2 rate was higher in the first molar (61.68%), and the isthmus rate was higher in the second molar (44.11%). DZ and SZ were thinner in MB2 than in MB1 at the maxillary molars with two mesial canals. The results indicated that more conservative preparation must be applied to the MB2 canal in the maxillary molars.